Conceptualizing and modeling relational processes in sociology : introducing disjointed fluidity - Joslyn, Jacqueline (Emerald Publishing Limited, 2022)
Sociologists have not neglected the study of relationships, but there remains no central definition of what a relationship is. Conceptualizing and Modeling Relational Processes in Sociology offers a definition of relationships that supports a conceptual tool and visualization technique for analyzing relational processes that are otherwise difficult to model using standard ethnographic and social network analysis techniques. Grounded in the work of social psychologists and relational sociologists and built on the premise that relationships are both remembered and imagined, Joslyn introduces disjointed fluidity: a new concept which maintains that relationships are molded by a flow of changing circumstances and dynamic cognitive processes. Featuring data from an ethnographic study of doctoral student mentorship, Joslyn uses this cutting-edge perspective to detail the mechanisms by which relationships are created, maintained, and dissolved. Pioneering a computational ethnographic technique that visualizes the properties and characteristics of relational processes, the author offers an exciting contribution to the efforts of relational sociologists to build a universal conceptualization of relationships. With broad appeal across scholars and graduate students in the social and behavioral sciences, Joslyn presents new ideas for expanding relationship modeling methods in a way that unites relationship scholars and extends relational theory. This is a captivating read for both methodologists and practitioners in relational fields, such as marketing, library sciences, criminal justice/legal psychology, and psychotherapy.
Keywords: Interpersonal relations -- Research -- Methodology.; Sociology.; Social Science -- Sociology / Social Theory.; Social theory.; elektronické knihy; electronic books